POLYCULTURE OF GIANT FRESHWATER PRAWN, MACROBRACHIUM ROSENBERG/I. WITH INDIAN MAJOR CARPS - A CASE STUDY - Vasudevappa, C.; Seenappa, D.; Keshavappa, G. Y. (Journal of Indian Fisheries Association, 2015)
A study conducted in a 450-m2 earthen pond to evaluate the production potential of giant freshwater prawn (stocked at 20,000 juveniles/ha) and Indian major carps, catla and rohu (stocked at 5000 juveniles/ha in 2:1 proportion) revealed that in nine months’ growing period, catla and rohu attained average sizes of 357 ang 746 g, respectively, while prawn weighed 48.32 g. The growth of rohu was much faster than catla as indicated by higher relative and absolute weight gains. The total fish production per hectare was estimated t.o be 2418 kg and prawn production stood at 780 kg with excellent survival of both the fish (>98%) and prawn (>80%). Keywords: Polyculture, giant freshwater prawn, Indian major carps